Bengkulu Naval Airbase Strategic Development in Enhancing National Defense - Suhirwan, Suhirwan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
The development of Bengkulu Naval Airbase is a strategic initiative to enhance Indonesia’s maritime defense capabilities, but various barriers have hindered its implementation. This study investigates the obstacles and supporting factors and provides actionable recommendations for its realization. This research uses the Suhirwan Quasy Qualitative methodological procedure comprising 13 distinct steps. In the initial phase, theoretical frameworks are utilized to construct structured interview guidelines for data collection. During the final phase, the same theoretical foundations serve to validate and confirm research findings derived from empirical data. The methodology combines theory and evidence through a two-phase approach: first as a design framework, then as an analytical validation tool. Data was collected through structured interviews and documentary studies from Navy officials, the Governor of Bengkulu, and stakeholders. The analysis uses triangulation to cross-check findings from multiple data sources and perspectives, ensuring rigor and validity. The findings emphasize the importance of leadership commitment, especially from the Bengkulu Governor, and effective coordination with the Ministry of Transportation. The study shows that developing the Bengkulu Naval Airbase is vital not only for maritime defense but also for boosting the local economy and community development. To address implementation challenges, the study recommends formalizing inter-agency coordination, optimizing resource distribution based on performance, and strengthening leadership support through accountability and training, all tailored to the military airbase context and informed by theory and practice. By addressing these factors, the Indonesian Navy can effectively develop the Bengkulu naval airbase, supporting broader national security goals.